Chromatin retained MUSHER lncRNA integrates ABA and DOG1 signalling pathways to enhance Arabidopsis seeds dormancy - Sacharowski, Sebastian Przemyslaw; Krzyszton, Michal; Brzezniak, Lien; Rogowski, Karol Jerzy; Montez, Miguel; Rosol, Katarzyna; Wrona, Magdalena; Yatusevich, Ruslan; Manjunath, Veena Halale; Szewc, Lukasz; Jarmolowski, Artur; Swiezewski, Szymon (Nature communications, 2025)
Many plant lncRNAs regulate gene expression by binding to chromatin, but how they are retained at the target loci is unclear. We identify a chromatin-localized lncRNA - MUSHER , which activates two parallel regulatory pathways to increase Arabidopsis seed dormancy. MUSHER is upregulated in response to high temperatures, contributing to the induction of secondary dormancy. It promotes DOG1 expression by recruitment of the CPSF complex to enhance the proximal cleavage and polyadenylation at the DOG1 transcript. It also increases ABA sensitivity in seeds by activating PIR1 gene transcription. These genes, located on different chromosomes, are both bound by MUSHER , despite lacking sequence homology. The chromatin association of MUSHER enables the integration of the DOG1- and ABA pathways to adjust seed germination timing. Additionally, MUSHER and other lncRNAs interact with U1 snRNP, which is required for their chromatin localisation, revealing a role for U1 snRNP in plants. Here the authors show that MUSHER lncRNA enhances Arabidopsis seed dormancy by integrating the ABA and DOG1 pathways. Chromatin retention of MUSHER and all other lncRNAs tested is mediated by U1 snRNP.